Utilization of land laws information in Nsangi and Katabi sub-counti es in Wakiso district, Uganda - Ssettema, Daniel (Kampala, 2014)
Unpublished dissertation (MSc. Inf. Sc.) - Makerere University, 2014 .
Includes bibliographical references
Keywords: Land reform -- Law and legislation -- Utilization -- Uganda -- Wakis o district; Land tenure -- Laws and legislation -- Utilization -- Uganda -- Waki so district